Leafy legacy: Exploring the nutritional and cultural significance of traditional Kandyan leafy dishes in Sri Lanka - KulanathaI, G.P.R.; Keerthisinghe, S.M.M.D. (University of Colombo, 2025)
This study investigates the unique cultural and dietary significance of traditional Kandyan leafy vegetables in Sri Lanka. It aimed to analyze the historical role, nutritional value, and contemporary relevance of leafy vegetables to sustainable food practices, bridging traditional knowledge with modern science. Employing a mixed-methods approach, qualitative data were gathered until data saturation was reached, exploring the cultural significance, preparation methods, and perceived health benefits of selected leafy vegetable preparations from 17 adult interviews. These qualitative insights were systematically combined with a comprehensive scientific literature review (2014-2024) focusing on pharmacodynamics and phytochemical analysis. This integration was crucial for providing scientific corroboration for traditional dietary wisdom and contextualizing findings within modern nutritional understanding. Seven leafy vegetable preparations comprised 21.875% of the 32 dishes discussed. "Ala kola dalu anama" was most frequently mentioned by interviewees (31.25%), followed by "Thamberiya kola malluma" (9.375%). The remaining five leafy dishes were each mentioned by ~6.25% of interviewees. These preparations offer rich nutritional benefits for a balanced diet. Significantly, the study found Chavaya (Siviya) leaves used as a garnish (3.125%), highlighting Ayurvedic practices for digestive health. Findings underscore the potential of revitalizing traditional Kandyan leafy preparations to enhance modern diets and foster cultural appreciation. Promoting these nutrient-rich, culturally significant vegetables boosts local agricultural economies, enhances biodiversity, and strengthens sustainable food systems in Sri Lanka. Integrating this knowledge into health and nutrition programmes improves public health while preserving Sri Lanka's rich culinary heritage. This study contributes to understanding the nation's culinary traditions and their implications for sustainable living
Keywords: Kandyan cuisine; Leafy vegetables; Chavya garnishing; Sustainable food systems